Kemampuan Berpikir Kreatif Dan Metode Belajar Meningkatkan Nilai Mata Kuliah Kalkulus 2 Masa Pandemi Covid-19 - Cici Cahyana Amatullah (Peneliti.net, 2021)
During this pandemic, all nations of the world are required to take part in overcoming life's problems, including in the field of education. One of the ways taken in the field of education is to carry out online learning activities. The purpose of this research is to determine the effect of students' creative thinking abilities and methods. online learning on the value of calculus courses 2. The variables of this study were the ability to think creatively, online learning methods and grades of calculus subjects. Data were collected using observation techniques, questionnaires, tests, analyzed quantitatively. The results showed 72. 7% of the variable Value of the Calculus Course (Y) is determined by the variable factor of creative thinking ability (X1) and learning method (X2) while the remaining 27. 3% is determined by other factors, 54. 4% of the variable value of calculus2 (Y) is determined by the variable factor of creative thinking ability. (X1), 59. 5% of the variable value of the 2 calculus course (Y) is determined by the variable factor el online learning method (X2). This study only reveals internal factors, namely the ability to think creatively and online learning methods, even though there are many other factors that can affect the value of calculus courses 2. Weaknesses found in this study need to be followed up with research the next which is related and relevant to the problems contained in this study